First isolation of a new type of human adenovirus (genotype 79), species Human mastadenovirus B (B2) from sewage water in Japan - Yoshitomi, Hideaki; Sera, Nobuyuki; Gonzalez, Gabriel; Hanaoka, Nozomu; Fujimoto, Tsuguto (Journal of medical virology, 2017)
Human mastadenoviruses (HAdVs) are highly infectious viral pathogens that survive for prolonged periods in environmental waters. We monitored the presence of HAdVs in sewage waters between April 2014 and March 2015. A total of 27 adenoviral strains were detected in 75% (18/24 in occasion‐base) of 24 wastewater collected samples. We identified the types of the strains as HAdV‐C2 (n = 5), HAdV‐A31 (5), HAdV‐C1 (4), HAdV‐B3 (4), HAdV‐C5 (4), HAdV‐B11 (2), P11H34F11 (2), and HAdV‐D56 (1). The complete genome sequence of one P11H34F11 (strain T150125) was determined by next‐generation sequencing and compared to other genome sequences of HAdV‐B strains. The comparisons revealed evidence of a recombination event with breaking point in the hexon encoding region, which evidenced high similarity to HAdV‐B34, while half of the rest of the genome showed similarity to HAdV‐B11, including regions encoding fiber and E3 region proteins. The penton base encoding region seemed to be a recombinant product of HAdV‐B14, ‐34; however, it was evidenced to be divergent to both as a novel type despite showing low bootstrap to support a new clade. We propose T150125 (P11H34F11) is a strain of a novel genotype, HAdV‐79. These results support the usefulness of environmental surveillance approaches to monitor circulating HAdVs including novel types.